English One Day Bersama Anak-Anak SD Negeri 015 Kelurahan Kariangau Kecamatan Balikpapan Barat - Khotimah, Husnul; Latumeten, Anna Anganita Theresia; Christiana, Yessica Martha (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Development and progress in various areas of life require individuals to develop their knowledge. One of them is regarding language, English is primarily a foreign language that has an important role in everyday life. Children must begin to be introduced to and taught English so that they are not trapped in ignorance. One form of student service to the community is by holding an "English One Day" activity for grade 2 students at SD Negeri 015 Balikpapan Barat, Kariangau District to introduce English to children to prepare the next generation and strengthen relations between the community. with the university. Keywords: Education,  English Language, Service